2021
DOI: 10.3846/tede.2021.14223
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling Consumer Satisfaction Based on Online Reviews Using the Improved Kano Model From the Perspective of Risk Attitude and Aspiration

Abstract: With the development of e-commerce, an increasing number of online reviews can serve as a promising data source for enterprises to improve online products. This paper proposes a method for modelling consumer satisfaction based on online reviews using the improved Kano model from the perspective of risk attitude and aspiration. Firstly, the attributes concerned by consumers are extracted from online reviews, and sentiment analysis of the extracted attributes is carried out using Standford CoreNLP. Secondly, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Existing studies suggested that online textual reviews indicate details on customers' demands and perceptions of hotel attributes [6,9]. Although numerical textual reviews have been studied widely to extract critical hotel attributes and their sentiment [14,15,46], few studies have distinguished between positive reviews and negative reviews to identify wellperformed attributes contributing to satisfied customers and poorly performed attributes resulting in dissatisfied customers. Therefore, this study attempts to explore the difference between the good performance and poor performance of the same attribute with respect to positive reviews and negative reviews concerning different star hotels through sentiment analysis.…”
Section: Studies On Hotel Online Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies suggested that online textual reviews indicate details on customers' demands and perceptions of hotel attributes [6,9]. Although numerical textual reviews have been studied widely to extract critical hotel attributes and their sentiment [14,15,46], few studies have distinguished between positive reviews and negative reviews to identify wellperformed attributes contributing to satisfied customers and poorly performed attributes resulting in dissatisfied customers. Therefore, this study attempts to explore the difference between the good performance and poor performance of the same attribute with respect to positive reviews and negative reviews concerning different star hotels through sentiment analysis.…”
Section: Studies On Hotel Online Reviewsmentioning
confidence: 99%
“…Based on the TF-IDF algorithm, we obtained the weight of each sub-attribute with respect to the six attributes concerning four hotel star ratings. Then the importance of the six attributes concerning four hotel star ratings was calculated respectively by Equation (15), as shown in Table 11. On the whole, the importance of value, service and sleep quality varies across the hotel star ratings, while other attributes' importance fluctuates slightly and are considered as very important for all hotels.…”
Section: The Ipa Plotmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen et al [14] measured consumer satisfaction along with several consumer behavior factors (e.g., emotion, loyalty, and trust). However, existing research mainly evaluates the relationship between product (or service) attributes [35]- [38] and consumer satisfaction through subjective methods [39], such as questionnaires, interviews, etc., most of which focus on customer perceptions and attitudes instead of more concrete objective criteria [20]. Besides, according to the definition of user satisfaction in these studies [24], [34], consumers' evaluation behavior should be a considered process, and the satisfaction score is a well-thought-out result generated in evaluation process.…”
Section: Literature Review a Consumer Satisfaction And Evaluationmentioning
confidence: 99%
“…In conclusion, satisfaction decision-making is the result of consumers' well-thought-out evaluation process. Although user satisfaction has been extensively studied by scholars both in the field of data mining [35]- [38] and traditional empirical research [39]. However, most of these studies only focus on product attributes, few studies have fully explored the effect of consumer heterogeneity (personality characteristics) on satisfaction decision making.…”
Section: Literature Review a Consumer Satisfaction And Evaluationmentioning
confidence: 99%